Rapid Screening of Drug-Protein Binding Using High-Performance Affinity Chromatography with Columns Containing Immobilized Human Serum Albumin. (28th March 2013) - Li, Ying-Fei; Zhang, Xiao-Qiong; Hu, Wei-Yu; Li, Zheng; Liu, Ping-Xia; Zhang, Zhen-Qing
Abstract : For drug candidates, a plasma protein binding (PPB) more than 90% is more meaningful and deserves further investigation in development. In the study, a high-performance liquid chromatography method employing column containing immobilized human serum albumin (HSA) to screen in vitro PPB of leading compounds was established and successfully applied to tested compounds. Good correlation (a coefficient correlation of 0.96) was attained between the reciprocal values (X ) of experimentally obtained retention time of reference compounds eluted through HSA column and the reported PPB values (Y ) with a correlation equation ofY = 92.03 − 97.01 X . The method was successfully applied to six test compounds, and the result was confirmed by the conventional ultrafiltration technique, and both yielded equal results. However, due to the particular protein immobilized to column, the method cannot be applied for all compounds and should be exploited judiciously based on the value of the logarithmic measure of the acid dissociation constant (pKa) as per the requirement. Ifα 1-acid glycoprotein and other plasma proteins could be immobilized like HSA with their actual ratio in plasma to column simultaneously, the result attained using immobilized column may be more accurate, and the method could be applied to more compounds without pKa limitation.